Vertical bacterial variability in oxidation ponds in the tropical zone - C. Tudsanaton; T. Pattamapitoon; O. Phewnil; W. Wararam; K. Chunkao; P. Maskulrath; M. Srichomphu (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Community domestic wastewater contains organic substances that can be decomposed through natural processes. Treatment using oxidation pond systems is popular in tropical zones because these locations provide a climate suitable for the growth and organic decomposition activities of various bacteria that remove organic contaminants from wastewater. Given that bacteria play an important role in the biodegradation of organic substances in wastewater treatment plants, their degradation activity is used as an indicator of water quality. The purpose of this study is to examine the vertical variability of bacteria in natural treatment oxidation ponds in tropical zones.METHODS: Wastewater samples were collected from an oxidation pond at 3 different depths (0–0.6, 0.6–1.5 and more than 1.5 meter), and their chemical, physical and biological qualities were analysed. Next-generation sequencing techniques were used to identify bacterial diversity, and the water quality at each depth was applied as an indicator of bacterial degradation activities.FINDINGS: Community domestic wastewater contained 10 major bacterial phyla that differed at different depths. Amongst these phyla, the Actinobacteriota dominated (25.35 to 28.23 percent), followed by Cyanobacteria (19.49 to 21.57percent), Planctomycetota (15.50 to 17.41 percent), Firmicutes (9.97 to 10.79 percent), Proteobacteria (9.73 to 10.79 percent), Verrucomicrobiota (6.47 to 7.69 percent), Chloroflexi (2.79 to 2.99 percent), Bacteriota (0.96 to 1.41 percent), Acidobacteriota (0.70 to 0.80 percent) and SAR324 clade (marine group B) (0.69 to 0.61 percent). Four organic substances were found in contaminated domestic wastewater. 1) Photosynthetic cyanobacteria and phytoplankton performed aerobic degradation and accounted for the dissolved oxygen levels of 7.76, 7.45 and 7.42 milligrams per liter, respectively at various depths along the vertical profile. 2) Bacteria and archaeans that participate in carbon compound treatment included Planctomycetes, Verrucomicrobiota, Bacteroidota and Euryarcheota. These bacteria exhibited a treatment efficiency for biochemical oxygen demand and low abundance at all depths. Biological oxygen demand increased to 23.11, 24.27 and 34.48 milligrams per liter with depth. 3) Nitrogen-cycling bacteria included nitrifying and denitrifying bacteria. They belonged to the Actinobacteriota, Planctomycetota, Firmicutes, Verrucomicrobiota, Chloroflexi, Bacteriota, Protrobacteria and Acidobacteriota phyla. They exhibited an ammonia-nitrogen treatment efficiency of 91.73 percent. 4) Phosphorus cycling–related bacteria in the Actinobacteriota phylum presented the orthophosphorus treatment efficiency of 65.41 percent.CONCLUSION: The results of this study suggested that bacterial communities did not significantly differ along oxidation depth because they work together with chemotrophs, which participate in organic substance decomposition, and phototrophs, which are involved in oxygen generation and nutrient removal. All of the bacteria found in domestic wastewater benefit and support oxidation pond systems in tropical zones. Anaerobic bacteria can be found in wastewater and used in treatment systems due to their protective mechanisms against oxygen toxicity and self-repair mechanisms. The knowledge gained from this study can be used as a reference in future works on natural wastewater treatment systems.